Measuring the brittle-to-ductile transition temperature of tungsten–tantalum alloy using chevron-notched micro-cantilevers. (15th April 2020) - Li, B.-S.; Marrow, T.J.; Armstrong, D.E.J.
Abstract: High-temperature micro-fracture tests of a industrial grade W–1%Ta alloy were performed from room temperature up to 700 °C, using chevron-notched micro-cantilevers. A gradual increase of conditional fracture toughness (KQc ) was measured with increasing temperature, and a microscale brittle-to-ductile transition temperature (BDTT) was found at 600 °C. This is slightly higher than macroscopic three-point bending tests from the same material ( 400 °C), and contradicts most literatures for pure tungsten that shows a significant lower micro-BDTT. The results suggested that the BDTT is independent of the specimen size, and the higher micro-BDTT is due to the tantalum in this alloy. Graphical abstract: Image, graphical abstract